POTENSI PEMANFAATAN KAYU GELAM DAN KAYU SENGON DALAM DUNIA KONSTRUKSI BERDASARKAN UJI KUAT LENTUR - Basyaruddin, Basyaruddin; Suryaningsih, Alnovia -; Awali, Jatmoko (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2019)
In 2013, The Ministry of Forestry revealed that the need for wood as material for construction was always increasing. In order to find the innovations regarding timber structure, this study was conducted to discover the flexural strength of gelam and sengon based on SNI 03-3959-1995. Also, specimens which 50 mm in depth, 50 mm in height and 760 mm in length were tested using two point loading method based on ASTM D-198. This research showed that the average flexural strength of gelam is 100.13 Mpa which is greater than sengon (82.62 Mpa). Furthermore, as simple truss structure, simulation indicated that gelam and sengon are still capable in resisting moment generated from service load.